Interactions among lactose, spray-dried animal plasma, and soybean meal levels may affect segregated early-weaned pigs - W B Nessmith Jr; J R Bergstrom; J A Loughmiller; R E Musser; K Q Owen; J W Smith II; B T Richert; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1995)
Pigs weaned in a segregated early weaning (SEW) environment achieved maximum performance when fed a sequence of diets containing a gradual decrease in spray-dried animal plasma. Furthermore, pigs weaned at approximately 19 days responded positively to 20% soybean meal. Increased levels of lactose enhanced the increases in performance from soybean meal.; Swine Day, Manhattan, KS, November 16, 1995
Keywords: Swine day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-140-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 746; Swine; Lactose; Spray-dried plasma; Soybean meal; Early-weaned pigs